Determinants of roundworms among primary school students in North Sumatera Province, Indonesia - Vierto Irennius Girsang; Friska Vaulina Manik; Seri Asnawati Munthe (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2019)
Background: Worm infection was an environment-based disease caused by nematode class worms’ intestine and transmitted through the soil. This condition could effect to their ability in school-age children to pay attentiont during the lessons.Purpose: To determine the determinants of roundworms in elementary school students in Silahisabungan Subdistrict (Dairi) , North Sumatera, Indonesia.Methods: The case-control design with a total sample of 150 students taken from 5 elementary schools starting in grade 5 and 6. This research instrument used a questionnaire.Results: That there was no effect between hand washing habits at OR 1.90 (95% Cl: 0.697 - 5.180), there was no effect on nail hygiene by OR 1.19 (95% Cl: 0.505-2828), there was no the influence of footwear use amounting to OR 1.68 (95% Cl: 0.672-2225), there was an influence of the source of clean water of OR = 17.17 (95% Cl: 1,800-1 163,78) and there is an effect of providing latrines at OR = 5.55 (95% Cl : 1,128-27,398).Suggestion: To students to be pay more attention in their personal hygiene, propose to teachers to be able to regularly check the student hygiene such as nail hygiene and make a source of information media in the school environment. Finally, this study asked the health centers to conduct child health screening and conduct counseling about personal hygiene.